Pembimbingan Tes Intelegensi Umum Calon Pegawai Negeri Sipil di Kota Sorong: Studi Kasus Pada Pembimbingan Matematika dan Analisis kasus - Rabiudin, Rabiudin; Katmas, Ekarina (Solidaritas: Jurnal Pengabdian, 2022)
This service activity aims to improve the skills of test-takers in solving general intelligence test questions for prospective civil servants in 2021. The method used in this service is participatory action research which involves collaboration with participants through actions given by the trainer as well as a facilitator. The action is in the form of delivering material, giving information on how to quickly solve problems, and tiered exercises. An important finding in this service is that students who are guided in following explanations and exercises well, meanwhile through pre-test and post-test data, it is concluded that there is a gap in mathematical insight and case analysis for civil servant enthusiasts from the natural sciences department or allied with graduates from majoring in social sciences or a cognate. This difference in responses and learning outcomes becomes a follow-up in the next service with different treatments.